Service Attribute Boundary Conditions of the Service Climate–Customer Satisfaction Link - Mayer, David M.; Ehrhart, Mark G.; Schneider, Benjamin (Academy of Management Journal, 2009)
We propose service attributes as boundary conditions of the relationship between service climate and customer satisfaction. Drawing on service climate theory and research, the customer contact model of service delivery, typologies of service attributes, and relational coordination theory, we hypothesized that customer contact frequency, service intangibility, and service employee interdependence moderate the positive link between service climate and customer satisfaction so that the relationship is more positive when those three variables are at high levels. Using a sample of 129 supermarket departments, we collected data from three unique sources (service employees, executives, and customers). Analyses revealed support for the hypotheses.